2011
DOI: 10.1590/s1519-69842011000500017
|View full text |Cite
|
Sign up to set email alerts
|

Management and relocation of nests of Podocnemis expansa (Schweigger, 1812) (Testudines, Podocnemididae) on the Crixás-Açu river, Brazil

Abstract: Podocnemis expansa nests in the sandbanks of the Crixás-Açu River in central Brazil during the dry season. With the return of the rainy season, the river banks are once again inundated, flooding nests and eggs and drowning hatchlings. This study evaluated relocation as an alternative to manage nests at risk of flooding. Forty P. expansa nests from four beaches of the Crixás-Açu were relocated to nurseries constructed in tanks filled with sand from the same river. Nine nests were covered with palm fronds to sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This result is similar to data of Platt et al (2008) who found 27% of all C. moreletii nests flooded in Belize. As in other reptiles nesting near water bodies, they search for the most suitable sites for nesting, females must choose sites that are topographically high enough to prevent the flooding of nests at the start of the rainy season (Gomes and Ferreira Júnior, 2011;Alves-Júnior et al, 2012). The rise in the water level of Lago de Catemaco is caused by rainfall excess, but we believe that the dam control in the lake may constitute a threat to the crocodile populations.…”
Section: Discussionmentioning
confidence: 97%
“…This result is similar to data of Platt et al (2008) who found 27% of all C. moreletii nests flooded in Belize. As in other reptiles nesting near water bodies, they search for the most suitable sites for nesting, females must choose sites that are topographically high enough to prevent the flooding of nests at the start of the rainy season (Gomes and Ferreira Júnior, 2011;Alves-Júnior et al, 2012). The rise in the water level of Lago de Catemaco is caused by rainfall excess, but we believe that the dam control in the lake may constitute a threat to the crocodile populations.…”
Section: Discussionmentioning
confidence: 97%
“…In many cases, particularly with sea turtles, climate change might induce an opposite response to that reported here; that is, warmer temperatures producing populations highly skewed toward females (Hawkes et al , Tomillo et al , Booth et al , Marcovaldi et al ). In such cases, males can be produced by cooling the substrate using water or shading the nest (Souza and Vogt , Gomes and Ferreira‐Júnior , Jourdan and Fuentes ). Shading strategies can be applied for gregarious nesters, but providing artificial shade for dispersive nesters would require an excessively high level of resources and effort (Wood et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Management of nesting beaches is a widespread conservation practice for endangered freshwater and sea turtle populations (Iverson , Janzen and Paukstis , Cantarelli et al , Revuelta et al ). Management activities include protection of the nests against predators, control of the vegetation surrounding nests, and nest transplantation to safer areas (Souza and Vogt , Yerli et al , Gomes and Ferreira‐Júnior , Jourdan and Fuentes ). Such activities can have a substantial impact on nest survivorship, sex ratio, and hatchling fitness.…”
mentioning
confidence: 99%
“…The most studied reproductive pattern of the Giant Amazon River turtle is the process of nesting (Alho and Padua, 1982;Gomes and Ferreira Junior, 2011;Alves-Junior et al, 2012).…”
Section: Introductionmentioning
confidence: 99%